2003
DOI: 10.1038/sj.npp.1300248
|View full text |Cite
|
Sign up to set email alerts
|

Immune Activation During Pregnancy in Rats Leads to a PostPubertal Emergence of Disrupted Latent Inhibition, Dopaminergic Hyperfunction, and Altered Limbic Morphology in the Offspring: A Novel Neurodevelopmental Model of Schizophrenia

Abstract: Prenatal exposure to infection is associated with increased liability to schizophrenia, and it is believed that such an association is mediated by the maternal immune response, in particular, the proinflammatory cytokines released by the maternal immune system, which may disrupt fetal brain development. Impaired capacity to ignore irrelevant stimuli is one of the central deficits in schizophrenia, and is manifested, among others, in loss of latent inhibition (LI), a phenomenon whereby repeated inconsequential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
360
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 445 publications
(392 citation statements)
references
References 100 publications
29
360
2
1
Order By: Relevance
“…Hence, we confirm here that maternal PolyI:C exposure can lead to functional deficits in multiple neuropsychological domains in the grown offspring, [14][15][16][17][18][19] and further reveal that the macrophagespecific overexpression of IL-10 in the maternal host can prevent the expression of the behavioral and cognitive deficits induced by prenatal immune activation. In the absence of a discrete inflammatory stimulus, however, enforced IL-10 overexpression by itself is linked to specific behavioral abnormalities in the form of deficient spatial exploration and associative learning.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Hence, we confirm here that maternal PolyI:C exposure can lead to functional deficits in multiple neuropsychological domains in the grown offspring, [14][15][16][17][18][19] and further reveal that the macrophagespecific overexpression of IL-10 in the maternal host can prevent the expression of the behavioral and cognitive deficits induced by prenatal immune activation. In the absence of a discrete inflammatory stimulus, however, enforced IL-10 overexpression by itself is linked to specific behavioral abnormalities in the form of deficient spatial exploration and associative learning.…”
Section: Resultssupporting
confidence: 83%
“…Here, we focused on adult spatial exploration, sensorimotor gating and selective associative learning, because previous reports in rodents have repeatedly demonstrated that prenatal PolyI:C exposure leads to functional abnormalities in these neuropsychological domains when the animals reach adult age. [14][15][16][17][18][19] First, spatial exploration was studied in an open field by focusing on the time the animals spent in the central area of the field during a 30-min test period. This test is widely applied to assess explorative behavior in rodents.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations